IMPLEMENTASI KEBIJAKAN PROGRAM KELUARGA HARAPAN (PKH) DALAM PENANGGULANGAN KEMISKINAN DI KECAMATAN DENGILO KABUPATEN POHUWATO - Iskandar Ibrahim (Universitas Islam Darul Ulum Lamongan, 2022)
This study aims to determine how the policy implementation of the Family Hope Program (PKH) in poverty alleviation in Dengilo District, Pohuwato Regency. The method in this research is descriptive research with a qualitative approach. Informants in this study use the purposive sampling technique from population units that are considered key informants, namely those who are directly involved and related to the implementation of PKH policies. The results showed that the goals and objectives of the Family Hope Program (PKH) in Dengilo sub-district can be stated to have been right on target and the objectives of the PKH implementation have been achieved well starting from the mechanisms and procedures, the suitability of the amount of assistance received by participants has gone well and in accordance with general guidelines for the implementation of PKH; Resources in the implementation of PKH in the Dengilo sub-district are very good in carrying out their duties, besides that they also receive direct training from the Ministry of Social Affairs of the Republic of Indonesia, related to the implementation of PKH; Socio-Economic Conditions in the Dengilo sub-district, many people or KPM have social or economic conditions that concern, because the level of education, skills, public awareness of education and health is still low; Characteristics of implementing agents or assistants to KPM really empower themselves as objects and implement development and provide motivation to KPM; Communication between organizations in the implementation of PKH has gone well and smoothly, this can be seen by the division of the organizational structure and division of tasks that is quite good and has a formal meeting which is held once a month.